Can the scaling behavior of electric conductivity be used to probe the self-organizational changes in solution with respect to the ionic liquid structure? The case of [C8MIM][NTf2]1. Issue 32 (28th August 2015) - Paluch, Marian; Wojnarowska, Zaneta; Goodrich, Peter; Jacquemin, Johan; Pionteck, Jürgen; Hensel-Bielowka, Stella
<x xml:space="preserve">Abstract</x> Scaling exponent as a key parameter to probe self-organization changes in solution with respect to the IL structure.